The Influence of Management Information Systems on Teacher Performance at UPTD in Kampung Rakyat District, South Labuhanbatu Regency - Dewi Ratna Bulan Siregar; Ilyas Prawiga (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2024)
Management Information Systems are one of the determinants in developing institutions in addition to professional human resources. Computerized management information systems are systems that tend to tie decision making closely to data processing systems and administrative work functions carried out using computers. This research aims to see the influence of the Management Information System (X) on Teacher Performance (Y) at the UPTD of Kampung Rakyat District, South Labuhanbatu Regency.The population in this study were teachers at the UPTD, Kampung Rakyat District, RegencySouth Labuhanbatu. The sample for this research consisted of 40 teachers. The data collection techniques used were questionnaires and documentation. The data analysis techniques used are simple linear regression analysis, hypothesis testing (t test), and coefficient of determination to see how much the Management Information System contributes to Teacher Performance at the UPTD, Kampung Rakyat District, South Labuhanbatu Regency.Based on the research results, it shows that: (1.) Management information systems have a significant effect on teacher performance at UPTD, Kampung Rakyat District, RegencySouth Labuhanbatu with a calculated t value of 3.653 and a sig value. of 0.001. (2.) The influence of management information systems on teacher performance at UPTD, Kampung Rakyat District, South Labuhanbatu Regency is 94.5%, while the remaining 5.5% is influenced by other variables that are not in this research.